CONTRIBUTION OF FISH CONSUMPTION TO CADMIUM AND LEAD INTAKES IN COASTAL COMMUNITIES OF WEST KALIMANTAN, INDONESIA - Arifin, Zainal; Falahudin, Dede (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2017)
Consumption of both marine and freshwater fishes is considered as a healthy way to obtain diet, but the ingestion of contaminated fishes remains a concern. Our study is conducted to asses cadmium (Cd) and lead (Pb) contents in various fishes consumed by coastal communities in six districts of West Kalimantan (Indonesia) and their health risks to the communities. Specifically, the objectives of this study are to determine the average weekly intakes (AWIs) of cadmium and lead based on dietary intake of fishes, then estimate health risk associated with fish consumption using the risk quotients (RQs) method. We also use food frequency questionnaires (FFQ) filled by 696 respondents to assess fish consumption habit of the communities in West Kalimantan who consumed up to 30 fish species in 2012 and 2013. Our results show that their average weekly fish consumption is 135.7 ± 66.3 g/week, which contributes to AWI values of 0.38 ± 0.55 ?g/kg body weight (bw) per week for Cd and 0.87 ± 0.65 ?g/kg bw per week for Pb. The RQ values indicate a low risk of Pb coming from fish consumption, but the RQ value for Cd is high for the children age group. In conclusion, fish consumption in the six districts of coastal communities in West Kalimantan generally does not pose any health risk from Pb. Conversely, Cd intake from fish consumption has a potential risk for children. As such, regular monitoring and additional studies are needed on potential contribution of Cd intake from other food sources.